Becoming Chinese American: A History of Communities and Institutions - Lai, Him Mark (Rowman & Littlefield Publishers, 2004)
Becoming Chinese American discusses the historical and cultural development of Chinese American life in the past century. Representing a singular breadth of knowledge about the Chinese American past, the volume begins with an historical overview of Chinese migration to the United States, followed by critical discussion of the development of key community institutions, Chinese-language schools, newspapers, and politics in early Chinese American life. Rather than emphasize experiences of discrimination, the collection focuses on Chinese American community formation that tested the racially-imposed boundaries on their new lives in the United States. Written by noted Chinese American scholar Him Mark Lai, the essays in this volume will be of interest to scholars of Asian and Asian American studies, as well as American history, ethnicity, and immigration.